基于Citespace的国际汉语教学设计研究现状与发展趋势研究 - KYI, HTWE (Journal of Maobi, 2025)
International Chinese language teaching plays a pivotal role in promoting the global development of the Chinese language. Effective teaching design is essential for ensure coherent, fluent, and high-quality teaching. To provide a comprehensive overview of the development in this field, this study employs CiteSpace to conduct a visualization-based bibliometric analysis of 6,962 CNKI publications from 2003 to 2023, examining publication trends, institutional contributions, keyword clusters, and citation bursts. The findings reveal a steady increase in research output, with constructivism serving as the primary theoretical foundation. Error analysis and case-based teaching designs are widely used, with research focusing on task-based activities, classroom processes, and integrated course design. However, writing instruction and studies on non-ethnic Chinese learners, beginners, and intermediate or advanced learners remain underexplored. Micro-level research on classroom practices dominates the field,while macro-level studies on curriculum development, teaching systems, syllabus design, and digital resource development are relatively scarce. In recent years, the rise of educational technologies and new national educational initiatives has brought cultural instruction, online teaching, and the integration of ideological-political elements into the curriculum to the forefront, reflecting a shift from purely language-skill-oriented designs toward comprehensive paradigms that integrate language, culture, and values. This study provides a systematic overview of the field, identifies evolving research hotspots, and offers insights for enhancing international Chinese teaching design.